1999
DOI: 10.3354/ame018247
|View full text |Cite
|
Sign up to set email alerts
|

Relations between bacterial nitrogen metabolism and growth efficiency in an estuarine and an open-water ecosystem

Abstract: Bacterial uptake or release of dissolved nitrogen compounds (amino nitrogen, urea, ammonium and nitrate) were examined in 0.8 pm filtered water from an estuary (Santa Rosa Sound [SRS], northwestern Florida) and an open-water location in the Gulf of Mexico (GM). The bacterial nutrient dynamics were related to oxygen consumption and activity of enzymes involved in nitrogen assimilation (glutamate dehydrogenase [GDH], glutamine synthetase [GS] and aminopeptidase activity [leu-MCA]). Dissolved free amino acids (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 41 publications
3
38
1
2
Order By: Relevance
“…The C : N s ratio and multiple substrate sources-Our current results confirm our previous conclusions (Goldman and Dennett 1991) and those of Tupas and Koike (1990;1991) that cometabolism of amino acids and NH 4 ϩ is a common occurrence in marine bacteria and that there is absolutely no evidence that NH 4 ϩ uptake is inhibited in the presence of amino acids, as has been suggested previously (Kirchman et al 1989;Kirchman 1994;Jorgensen et al 1999). The key factor regulating the uptake of NH 4 ϩ is the availability of a carbon source to provide a stoichiometric balance between C and N uptake, as regulated by the C : N B ratio and GGE of the bacterial population.…”
Section: Discussionsupporting
confidence: 92%
“…The C : N s ratio and multiple substrate sources-Our current results confirm our previous conclusions (Goldman and Dennett 1991) and those of Tupas and Koike (1990;1991) that cometabolism of amino acids and NH 4 ϩ is a common occurrence in marine bacteria and that there is absolutely no evidence that NH 4 ϩ uptake is inhibited in the presence of amino acids, as has been suggested previously (Kirchman et al 1989;Kirchman 1994;Jorgensen et al 1999). The key factor regulating the uptake of NH 4 ϩ is the availability of a carbon source to provide a stoichiometric balance between C and N uptake, as regulated by the C : N B ratio and GGE of the bacterial population.…”
Section: Discussionsupporting
confidence: 92%
“…There is presently very little research on variations in BR cell Ϫ1 in either freshwater (Cimbleris and Kalff 1998) or marine waters (Jorgensen et al 1999). However, our results would argue that, while BR may often be rather invariant in aquatic ecosystems, BR cell Ϫ1 is highly variable and perhaps the more appropriate scale when considering how variations in respiration relate to BGE.…”
Section: Discussionmentioning
confidence: 72%
“…In two streams in Sweden, 19 to 55% of the bulk DON was found to be bioavailable in short-term bioassays (Stepanauskas et al, 2000); only 5 to 18% of the DON was identified as urea, DCAA or DFAA indicating that bacteria also utilize additional organic N compounds. In the Gulf of Riga, 13% of the DON was bioavailable during 7 to 8 day bioassay experiments (Jørgensen et al, 1999).…”
Section: Results From Bioassaysmentioning
confidence: 99%